2018
DOI: 10.3389/fnana.2018.00021
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of White Matter Integrity and Hippocampal Functional Connectivity in Type 2 Diabetes Without Mild Cognitive Impairment

Abstract: Aims: To investigate the white matter (WM) integrity and hippocampal functional connectivity (FC) in type 2 diabetes mellitus (T2DM) patients without mild cognitive impairment (MCI) by using diffusion tensor imaging (DTI) and resting-state functional magnetic resonance imaging (rs-fMRI), respectively.Methods: Twelve T2DM patients without MCI and 24 age, sex and education matched healthy controls (HC) were recruited. DTI and rs-fMRI data were subsequently acquired on a 3.0T MR scanner. Tract-based spatial stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 45 publications
(57 reference statements)
2
41
0
Order By: Relevance
“…However, there were no comprehensive and sensitive assessments on cognitive function, or subjects in these studies were older. Sun et al found that functional connectivity (FC) between the hippocampus and certain brain structures had decreased significantly in T2DM subjects without MCI (12). However, results of the region of interest (ROI)-based FC analysis should be interpreted in caution, as the selected ROIs are mainly based on the prior knowledge, leading to different and unpredictable findings (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, there were no comprehensive and sensitive assessments on cognitive function, or subjects in these studies were older. Sun et al found that functional connectivity (FC) between the hippocampus and certain brain structures had decreased significantly in T2DM subjects without MCI (12). However, results of the region of interest (ROI)-based FC analysis should be interpreted in caution, as the selected ROIs are mainly based on the prior knowledge, leading to different and unpredictable findings (13).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies focused not only on the comparison between T2DM subjects and healthy controls, but also on the differences between those with and without cognitive impairment . Decreased hippocampal functional connectivity with the bilateral frontal cortex has been found for T2DM patients without MCI . Yang et al compared T2DM subjects with and without cognitive impairment with healthy controls, and found impaired intranetwork and internetwork connectivities, especially in those with MCI .…”
mentioning
confidence: 99%
“…A number of neuroimaging studies have emerged to investigate the abnormal brain functions of T2DM patients by measuring alterations in the spontaneous brain activities at resting state, 4 executive and memory abilities at visual n-back task, 5 and interregion functional connectivities. [6][7][8] Some previous studies focused not only on the comparison between T2DM subjects and healthy controls, but also on the differences between those with and without cognitive impairment. 8,9 Decreased hippocampal functional connectivity with the bilateral frontal cortex has been found for T2DM patients without MCI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Resting-state FC can be used to evaluate interregional cooperation between different brain regions. Previous studies that examined different regions of interest (ROIs) other than the cerebellum have revealed the abnormal patterns of FC in T2DM (Musen et al, 2012;Chen et al, 2015;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%